Practical Acamity of The State of Immunity In Patients With Hypertension (Eurasian Medical Research Periodical, 2023)
According to modern concepts, lipid peroxidation (LPO) is a constantly occurring physiological process that, when intensified, is involved in the development of a number of pathologies. It has been established that activation of LPO processes is involved in the pathogenesis of many diseases of the cardiovascular system [2]. Lipid peroxides play an important role in the body: lipoperoxides are an important intermediate in the biosynthesis of prostaglandins E, progesterone; they are involved in the hydroxylation of the cholesterol core; they are necessary for activating a number of membrane processes and regulating membrane permeability.